Case Report: Hemophagocytic Lymphocytosis in a Patient With Glutaric Aciduria Type IIC - Huang, Lingtong; Wu, Wei; Zhu, Yijing; Yu, Huili; Tang, Lingling; Fang, Xueling (Frontiers in Immunology, 2022)
Hemophagocytic lymphocytosis (HLH) is a rare disease caused by inborn errors of immunity (IEI), secondary to infection, lymphoma or autoimmune disorders, but we often overlook the fact that HLH can be secondary to inborn errors of metabolism (IEM). Here, we describe a patient who was diagnosed with glutaric aciduria type IIC complicated by features suggestive of possible HLH. The diagnosis of glutaric aciduria type IIC, a IEM, was confirmed by whole exome sequencing. The patient was treated with coenzyme Q10 and riboflavin which effectively improved her liver function. During treatment, the patient developed severe anemia and thrombocytopenia. Persistent fever, splenomegaly, cytopenias, increased ferritin, hypertriglyceridemia, hypofibrinogenemia, and hemophagocytosis in the bone marrow pointed to the diagnosis of HLH; however, the patient eventually died of gastrointestinal bleeding. After other potential causes were ruled out, the patient was diagnosed with glutaric aciduria type IIC complicated by features suggestive of possible HLH. When cytopenias occurs in IEM patients, HLH is a possible complication that cannot be ignored. This case suggests a possible relationship between IEM and risk for immune dysregulation.